Effects of alkaline electrolyzed water pretreatment on the physicochemical quality attributes of fresh nectarine during storage. Issue 10 (19th August 2021) - Belay, Zinash A.; Botes, W. J.; Caleb, Oluwafemi J.
Abstract: Chlorinated water treatment has been extensively used to manage postharvest decontamination of fruits for decades. It has been well established that chlorine may produce undesirable by‐products that have a potential carcinogenic impact on human health and toxic waste on the environment. Electrolyzed water is an eco‐friendly technique that has been regarded as an effective method for decontaminating microbes on fruit surfaces. However, the impact of alkaline electrolyzed water (AEW) on the physical and biochemical quality attributes of nectarine fruit during postharvest storage is not fully understood. Therefore, this study investigated the effects of AEW treatment (200 mg/L, pH, 6.7), sodium hypochlorite, and nontreated (control) on the storability, quality attribute, and decay incidence of fresh nectarine stored at −0.5℃ and 95% RH for 31 days. Results obtained indicated that the AEW treatment effectively maintains firmness, reduced weight loss, and maintains high total soluble solid content with a slight decline in titratable acidity for nectarines. Furthermore, the AEW suppresses the decrease of color qualities of the peel L*, a*, b*, reduced the incidence of browning ( h° ) and surface decay compared with chlorine‐treated and control fruit. Novelty impact statement: Alkaline electrolyzed water (AEW) and its efficacy to minimize decay and maintain physicochemical quality of nectarine fruit compared with chlorinated water treatment were investigated. Treatment with AEW (200 mg/L, 10 min) effectively preserves the freshness of the nectarine fruit by reducing surface decay compared with the chlorine‐treated and control fruit. The outcome of this study provides guiding tools for stone fruit pack‐houses and other industry role players on the potential of EW as an alternative to chlorine treatments.